2023
DOI: 10.5114/ait.2023.125310
|View full text |Cite
|
Sign up to set email alerts
|

The use of preoperative inferior vena cava ultrasound to predict anaesthesia-induced hypotension: a systematic review

Abstract: Intraoperative hypotension after induction or initiation of anaesthesia is a common complication in clinical practice. It has been associated with poor patient outcomes including increased perioperative morbidity and even mortality [1]. Some special patient populations, such as the elderly and pregnant women undergoing caesarean section, are particularly prone to developing significant anaesthesia-induced hypotension (AIH) due to their unique physiological characteristics. Hypotension after induction of genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…There have been several previous studies attempting to predict SAH using TTE. Although the majority of them utilized inferior vena cava (IVC) diameter collapsibility, there was significant variation in predictability [ 7 , 17 , 18 ]. According to a recent meta-analysis, the maximum and minimum reported sensitivities of the IVC collapsibility index (IVCCI) for predicting SAH were 84.6% and 58.8%, respectively, whereas the maximum and minimum specificities were 93.1% and 23.5%, respectively [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several previous studies attempting to predict SAH using TTE. Although the majority of them utilized inferior vena cava (IVC) diameter collapsibility, there was significant variation in predictability [ 7 , 17 , 18 ]. According to a recent meta-analysis, the maximum and minimum reported sensitivities of the IVC collapsibility index (IVCCI) for predicting SAH were 84.6% and 58.8%, respectively, whereas the maximum and minimum specificities were 93.1% and 23.5%, respectively [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are studies that support the idea IVC ultrasonography is a reliable method when necessary technical and patient-related conditions are provided, current status of IVC ultrasonography in current anesthesia and ICU practice is questionable. 24 , 25 Recent data regarding previous studies have found significant heterogeneity in IVC ultrasonography methods both in ICU and in perioperative patients. 24 , 25 On the other hand, our study can be evaluated as a technical study, which aims to compare technical capability of two different devices for IVCD measurements rather than a clinical study that aims to decide fluid status or responsiveness in medical ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Recent data regarding previous studies have found significant heterogeneity in IVC ultrasonography methods both in ICU and in perioperative patients. 24 , 25 On the other hand, our study can be evaluated as a technical study, which aims to compare technical capability of two different devices for IVCD measurements rather than a clinical study that aims to decide fluid status or responsiveness in medical ICU patients. More randomized controlled studies should be done for understanding the place of PSUDs in daily ICU routine for different clinical conditions in which ultrasonography is capable of evaluating.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who developed hypotension in the current study had higher IVCCI, and they were older in age. Increasing age can be associated with increased respiratory variability of IVC [ 25 ]. Being at higher risk of dehydration, the older population may have higher IVCCI as a pathophysiologic response rather than just a confounder [ 6 ].…”
Section: Discussionmentioning
confidence: 99%